1997
DOI: 10.1128/jcm.35.12.3355-3357.1997
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Chlamydia trachomatis in urine samples by nucleic acid tests: comparison with culture and enzyme immunoassay of genital swab specimens

Abstract: Two commercially available nucleic acid-based tests, ligase chain reaction (LCR; Abbott Laboratories) and PCR (Roche Diagnostics), for the detection of Chlamydia trachomatis in male and female urine samples were compared with culture and enzyme immunoassay (EIA) (Microtrak; Syva) for C. trachomatis detection in genital samples. The samples were collected from 1,005 patients who attended a sexually transmitted disease clinic. In this study population, the prevalence of the infection was 4%. Specimens which were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
11
0
1

Year Published

1999
1999
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 21 publications
1
11
0
1
Order By: Relevance
“…While the manuscript was being prepared, two other studies reported similar results for the COBAS AMPLICOR test (14,26). These values are similar to those reported for the nonautomated AMPLICOR C. trachomatis test (2, 6, 25-28, 30, 35) and other amplificationbased C. trachomatis tests (1,6,7,9,14,18,23,25,26,30,33). Virtually identical performance was observed for urine and endocervical swab specimens from women.…”
Section: Discussionsupporting
confidence: 70%
“…While the manuscript was being prepared, two other studies reported similar results for the COBAS AMPLICOR test (14,26). These values are similar to those reported for the nonautomated AMPLICOR C. trachomatis test (2, 6, 25-28, 30, 35) and other amplificationbased C. trachomatis tests (1,6,7,9,14,18,23,25,26,30,33). Virtually identical performance was observed for urine and endocervical swab specimens from women.…”
Section: Discussionsupporting
confidence: 70%
“…For all samples with discrepant results (no inhibition was observed in these samples, as assessed by the internal control of the Amplicor assay), DNA was isolated from the original urine specimens and positivity for C. trachomatis was determined by an in-house PCR (17). By using serial dilutions of C. trachomatis serovar L2, the in-house test was 10 to 100 times more sensitive than the commercial assays, resulting in a detection limit of 1 inclusion-forming unit for the COBAS Amplicor and the LCx tests (identical sensitivity, as confirmed by others (26,33) and 0.1 to 0.01 inclusion-forming units for the in-house PCR, which is in agreement with sensitivities found previously (17).…”
Section: Resultsmentioning
confidence: 76%
“…Recently, DNA amplification techniques (Amplicor PCR [Roche Diagnostic Systems, Basel, Switzerland] [13,30] and ligase chain reaction [Abbott Laboratories, North Chicago, Ill.] [6,15]) and RNA amplification techniques AMPLIFIED Chlamydia Trachomatis Assay [AMP-CT; Gen-Probe] [5,7] and nucleic acid sequence-based amplification [Organon Teknika] [17,18]) have been successfully introduced for the diagnosis of C. trachomatis infections. They have the advantage of higher sensitivities and specificities compared to those of conventional techniques (3,25,26,29). However, the use of cervical and urethral swabs for screening for C. trachomatis infection in an asymptomatic population will result in low participation rates.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The target nucleic acid sequences are amplified by polymerase chain reaction (PCR) and the products (amplicons) detected in ethidium bromide-stained gels, or by colorimetric enzyme immunoassay. In order to amplify nucleic acids (DNA or RNA), these molecules need to be extracted and separated from other components of microorganisms or cellular materials that could inhibit amplification reactions [1][2]. Traditionally, guanidine isothiocyanate, followed by ethanol precipitation, has been used to obtain RNA from cells and microorganisms [3].…”
mentioning
confidence: 99%